Sentimental bodies : sex, gender, and citizenship in the early republic - Burgett, Bruce, 1963- (Princeton University Press, 1998)
Sentimentalism, sex, the construction of the modern body, and the origins of American liberalism all come under scrutiny in this rich discussion of political life in the early republic. Here Bruce Burgett enters into debates over the "public sphere," a concept introduced by Jurgen Habermas that has led theorists to grapple with such polarities as public and private, polity and personality, citizenship and subjection. With the literary public sphere as his primary focus, Burgett sets out to challenge the Enlightenment opposition of reason and sentiment as the fundamental grid for understanding American political culture.